posted by Kat on .
Rewrite the equation so that y is the fucntion of x:
Can you please explain and show how to do these two problems? Thank you.
Combine terms and put y alone on one side of the equation.
8x - 12y = -5x - 15y
Add 15y and subtract 8x from both sides.
3y = -13x
y = -13x/3
Do a similar process with the first equation.
I hope this helps. Thanks for asking.
Thanks a lot!
For b, it also says "use the result to find y when x=-1, 0, 2."
Can you please check this?
The last one should say: